SIKAP PERAN GENDER DALAM PEMBELAJARAN DI UHAMKA - Fajri, M. Dwi; Kumala, Anisia; Rosyidi, Muhib; Anjalie, Safira; Nurfadilah, Fatika (Jurnal Ilmiah Penelitian Psikologi, 2021)
Understanding gender roles is one of the important factors towards a bias-free society. This understanding or attitude is attached to the individual in at least two ways; exposure-based, where individuals gain an understanding through education, socialization, parental ideology, marital status, and interest-based where individuals gain an understanding of the benefits of certain gender ideologies for themselves. This study aims to provide an overview of gender role attitudes in UHAMKA students and al-Islam lecturers, especially in the Muamalah course, which is divided into egalitarian gender role attitudes and traditional gender role attitudes. There are five dimensions that are explored from gender role attitudes; religious views on gender, marriage and family, social roles, work and education. The study was conducted using a mixed method design, data collection methods were in the form of a survey for students regarding gender roles and in-depth interviews with lecturers of the Muamalah course. Respondents in this study were students and lecturers who graduated from the Muamalah course from the 2019/2020-2021/2022 academic year. The results of a survey of students illustrate that in the five dimensions measured in this study, most of the respondents have an egalitarian gender role attitude (70%). However, on certain items the survey results provide an illustration that respondents agree more with statements stating that the openness of women’s aurat is a source of harassment against women" and "women have difficulty making important decisions because women are dominated by feelings rather than logic". Meanwhile, the results of interviews with seven Muamalah lecturers obtained information that some respondents showed an egalitarian gender role attitude and some were traditional, especially in the dimensions of women’s social roles and education. Thus, this research can be the basis for mapping gender insights in the learning process at PTM campuses, especially at UHAMKA. The implications of this study will be discussed later.